Integration of Indian Knowledge Systems in Panchayatiraj Policies for Tribal Development: A Sociological Perspective - Jaimin J Chaudhary,; Dr. Mahendra Singh Parmar, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Panchayati Raj is not just a word but an outstanding example of India's self-sufficient village system, capable of meeting the needs of every individual. It is an essential part of decentralization of power and rural self-governance. Although the establishment of Panchayati Raj in modern times is often considered a new system, in reality, it has existed in a great country like India since ancient times. Indian traditional knowledge has deep-rooted administrative principles. For instance, the Arthashastra, written by the great scholar Kautilya, provides a detailed account of governance, emphasizing village administration and local self-governance. Similarly, during the late second and early third centuries, the Satavahana dynasty decentralized power to ensure the smooth administration of the state. This highlights that local governance was strong and effective even in ancient India. In modern India, the Panchayati Raj system is not only a pillar of rural development but also plays a crucial role in the development of tribal regions. The implementation of the PESA (Panchayats Extension to Scheduled Areas) Act has facilitated welfare programs for Van Bandhu (tribal communities), ensuring autonomy and empowerment for indigenous populations. Thus, the Panchayati Raj system is not merely an administrative structure but a vibrant and progressive system deeply connected to Indian traditional knowledge, village self-rule, and tribal empowerment.
Keywords: IKS; Panchayati Raj; PESA Act; Tribal development; Self governance